Grazing exclusion alters soil methane flux and methanotrophic and methanogenic communities in alpine meadows on the Qinghai–Tibet Plateau - Wang, Shilin; Chen, Xindong; Li, Wen; Gong, Wenlong; Wang, Zhengwen; Cao, Wenxia (Frontiers in Microbiology, 2023)
Grazing exclusion (GE) is an effective measure for restoring degraded grassland ecosystems. However, the effect of GE on methane (CH4) uptake and production remains unclear in dominant bacterial taxa, main metabolic pathways, and drivers of these pathways. This study aimed to determine CH4 flux in alpine meadow soil using the chamber method. The in situ composition of soil aerobic CH4-oxidizing bacteria (MOB) and CH4-producing archaea (MPA) as well as the relative abundance of their functional genes were analyzed in grazed and nongrazed (6 years) alpine meadows using metagenomic methods. The results revealed that CH4 fluxes in grazed and nongrazed plots were −34.10 and −22.82 μg‧m−2‧h−1, respectively. Overall, 23 and 10 species of Types I and II MOB were identified, respectively. Type II MOB comprised the dominant bacteria involved in CH4 uptake, with Methylocystis constituting the dominant taxa. With regard to MPA, 12 species were identified in grazed meadows and 3 in nongrazed meadows, with Methanobrevibacter constituting the dominant taxa. GE decreased the diversity of MPA but increased the relative abundance of dominated species Methanobrevibacter millerae from 1.47 to 4.69%. The proportions of type I MOB, type II MOB, and MPA that were considerably affected by vegetation and soil factors were 68.42, 21.05, and 10.53%, respectively. Furthermore, the structural equation models revealed that soil factors (available phosphorus, bulk density, and moisture) significantly affected CH4 flux more than vegetation factors (grass species number, grass aboveground biomass, grass root biomass, and litter biomass). CH4 flux was mainly regulated by serine and acetate pathways. The serine pathway was driven by soil factors (0.84, p < 0.001), whereas the acetate pathway was mainly driven by vegetation (−0.39, p < 0.05) and soil factors (0.25, p < 0.05). In conclusion, our findings revealed that alpine meadow soil is a CH4 sink. However, GE reduces the CH4 sink potential by altering vegetation structure and soil properties, especially soil physical properties.